Constraining and enabling factors of a successful regional policy in Europe - Ugo Fratesi (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Recent papers show that the impact of Cohesion Policy is not uniform in space but larger, smaller or insignificant depending on the regions. These outcomes mostly depend on the characteristics of each territory (conditioning factors). This paper reviews them and investigates, through descriptive statistical techniques, their presence in European regions. European regions are then classified in terms of need on two dimensions: GDP per capita and GDP growth. Results show that most policy favourable conditioning factors are also factors of growth. As a consequence of that, the potential policy impact is often larger in those regions which are less in need of support. In terms of policy consequence, cohesion policy should remain place-based and fully consider the regional specificities, as well the specificities of the various territories inside a region. However, since the conditioning factors for policy effectiveness are less present in regions more in need, acceptting trade-offs will be required, and in particular one between growth and policy effectiveness on one hand and territorial cohesion on the other. Lagging regions will also require interventions creating framework conditions, and those territorial assets which they are missing.
Keywords: R58; R11; R12; 330; Regional Policy; Cohesion; EU; Conditioning Factors